In Vitro Resistance of Víbrio Cholerae 01 Against 9 Antimicrobial Agents in Callao - Peru, April - June 1998 - Guevara Granados, José María (2000)
OBJECTIVE: To determine the current levels of in vitro resistance of Vibrio cholerae strains against different antimicrobial agents. MATERIALS AND METHODS: The in vitro resistance of 225 Vibrio cholerae strains isolated from stool cultures taken from patients at the "Hospital Nacional Daniel A. Carrión" and other health care centers of Callao, Peru, as part of the Epiderniologic Surveillance of the Acute Diarrheic Diseases and Cholera Programme,was assessed by disc-difusion method. RESULTS: Resistance patterns obtained were the following: 24,7% to ampicillin, 18,7% to tetracyclin, 8% to cotrirnoxazol, 7,5% to cephalotin, 5% to cloramphenicol, 2,25% to furazolidone, 1 % to nalidixic acid, 0,5% to norfloxacin and no resistance was observed to ciprofioxacin. It was also found 17,3% of cases with resistance to 2 or more antimicrobial agents. CONCLUSIONS: Antimicrobial resistance patterns of Vibrio cholerae are increasing in last years. Quinolones are still good therapeutic options in particular resistance cases.